Project management success or failure? : Manchester, 28 & 29 November 1979. (Thomas Telford, 1979)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in Manchester on 28-29 November 1979.
Keywords: Engineering -- Management -- Congresses.; Construction industry -- Management -- Congresses.; Project management -- Congresses.; elektronické knihy; electronic books